Synthesis and Characterization of Iron(III) Peroxy-Chromate - Richharia, Neelam; Bajpai, Rita; Tiwari, Sanjay; Tiwari, B.M.L. (Asian Journal of Chemistry, 2016)
Iron(III) chromate, FeCrO4(OH)·H2O, has been prepared with modified method and characterized by IR, Mössbauer, magnetic moment and elemental analysis. The prepared bluish-violet iron(III) peroxy-chromate belongs to violet series of peroxy-chromates. The isolated iron(III) peroxy-chromate has been formulated as Fe(Cr2O10)3. The probable mechanism of the formation of Fe[CrO(O2)2OH]3 and its transformation into stable Fe(Cr2O10)3 has also been worked out.